A study on the factors that influence students’ academic performance at Kolej Poly-tech Mara Kota Bharu / Siti Nurul Jannah Stapa - Stapa, Siti Nurul Jannah (2012)
Education industry needs to face an intense competition. The students’ academic performance plays an important role in producing the best quality of graduates. Students’ academic performance is importance for each institution. Thus, this study has been conducted to ascertain the factors that influence students’ academic performance at Kolej Poly-tech Mara Kota Bharu. A set of questionnaires was distributed to the respondent randomly. Several factors that being discussed in this research are socio-economic factor, psychological factor and environmental factor. The data is analyzed using descriptive analysis, reliability, correlation and regression analysis by using Statistical Package for Social Science (SPSS). Besides that, regression analysis was used to test the hypotheses in this study. In this research, the finding shows that psychological factor and environmental factor are significant to the students’ academic performance. Meanwhile, socio-economic factor was found to be insignificant to the students’ academic performance. Based on the results obtained, there are some suggested recommendations that can help Kolej Poly-tech Mara Kota Bharu to improve students’ academic performance